Learning During Coronavirus: “The Masque of the Red Death” - Jon Beasley-Murray (Modern Languages Open)
This reading of Poe’s “The Masque of the Red Death” emerges from a collaborative, online, transatlantic reading group that sprung up during the COVID-19 pandemic as an extension of homeschooling for a set of cousins and their parents. I ask what it means to read with children, and to learn from the ways in which children read. I suggest that, among other things, this involves reading more literally and less for metaphors and symbols or the other paraphernalia that tend to be features of formal teaching of literature in schools. Indeed, in the context of pandemic and lockdown, “The Masque of the Red Death,” if read with children or through a child’s eyes, might teach us very literally about enclosure and boundaries, about life and death, and about the always-failed ambitions of constituted power. It might teach us, moreover, about the ongoing importance of literature, and learning to read it well. We might seek to know things the way in which Virginia Woolf’s moth (in another struggle of life and death, read in the reading group) knows things: immanently, absolutely, with all the strength of the very weak.